Identifikasi Emisi CO₂ pada Penggunaan Lahan Permukiman di Kecamatan Mlati Kabupaten Sleman Yogyakarta - Dian Hudawan Santoso; Wisnu Aji Dwi Kristanto (Jurnal Mineral, Energi dan Lingkungan, 2020)
Carbon dioxide (CO2) is one of the greenhouse gas that play a role in increasing air temperature and global warming. The increasing trend of greenhouse gas over time requires estimation efforts for anticipation and reduction. This research was conducted Mlati sub district, Sleman Regency, Yogyakarta, in which there are types of rural and urban areas. This study aims to determine the amount of CO2 emissions in the form of settlement land and predict future CO2 emissions.The method used is Proportionate Stratified Random Sampling. Data collection using survey methods, questionnaires and interviews. The calculated variable is household domestic activity in the amount of cooking fuel, transportation fuel, used electric power and waste generated. Data analysis in this study used descriptive analysis, graphical analysis, statistical analysis, and spatial analysis CO₂rural emission value is 90,576,231.93 KgCO₂ / Year, urban 183.878.846,2 KgCO₂ / Year. CO2 emission projection value in Mlati sub-district for 2020: 380.966.673.9 KgCO₂ / Year, year 2025: 394.723.846,3 KgCO₂ / Year and year 2030: 408.481.018,7 KgCO₂ / Year Keywords: CO2 Emissions, Domestic Activities, Land use of Settlement